CYP3A variation, premenopausal estrone levels, and breast cancer risk. - Johnson, N; Walker, K; Gibson, L; Orr, N; Folkerd, E; Haynes, B; Palles, C; Coupland, B; Schoemaker, M; Jones, M; Broderick, P; Sawyer, E; et al. (2012)
BACKGROUND: Epidemiological studies have provided strong evidence for a role of endogenous sex steroids in the etiology of breast cancer. Our aim was to identify common variants in genes involved in sex steroid synthesis or metabolism that are associated with hormone levels and the risk of breast cancer in premenopausal women. METHODS: We measured urinary levels of estrone glucuronide (E1G) using a protocol specifically developed to account for cyclic variation in hormone levels during the menstrual cycle in 729 healthy premenopausal women. We genotyped 642 single-nucleotide polymorphisms (SNPs) in these women; a single SNP, rs10273424, was further tested for association with the risk of breast cancer using data from 10 551 breast cancer case patients and 17 535 control subjects. All statistical tests were two-sided. RESULTS: rs10273424, which maps approximately 50 kb centromeric to the cytochrome P450 3A (CYP3A) gene cluster at chromosome 7q22.1, was associated with a 21.8% reduction in E1G levels (95% confidence interval [CI] = 27.8% to 15.3% reduction; P = 2.7 × 10(-9)) and a modest reduction in the risk of breast cancer in case patients who were diagnosed at or before age 50 years (odds ratio [OR] = 0.91, 95% CI = 0.83 to 0.99; P = .03) but not in those diagnosed after age 50 years (OR = 1.01, 95% CI = 0.93 to 1.10; P = .82). CONCLUSIONS: Genetic variation in noncoding sequences flanking the CYP3A locus contributes to variance in premenopausal E1G levels and is associated with the risk of breast cancer in younger patients. This association may have wider implications given that the most predominantly expressed CYP3A gene, CYP3A4, is responsible for metabolism of endogenous and exogenous hormones and hormonal agents used in the treatment of breast cancer.